Th2 and eosinophil responses suppress inflammatory arthritis - Chen, Zhu; Andreev, Darja; Oeser, Katharina; Krljanac, Branislav; Hueber, Axel; Kleyer, Arnd; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2016)
Th2-eosinophil immune responses are well known for mediating host defence against helminths. Herein we describe a function of Th2-eosinophil responses in counteracting the development of arthritis. In two independent models of arthritis, Nippostrongylus brasiliensis infection leads to Th2 and eosinophil accumulation in the joints associated with robust inhibition of arthritis and protection from bone loss. Mechanistically, this protective effect is dependent on IL-4/IL-13-induced STAT6 pathway. Furthermore, we show that eosinophils play a central role in the modulation of arthritis probably through the increase of anti-inflammatory macrophages into arthritic joints. The presence of these pathways in human disease is confirmed by detection of GATA3-positive cells and eosinophils in the joints of rheumatoid arthritis patients. Taken together, these results demonstrate that eosinophils and helminth-induced activation of the Th2 pathway axis effectively mitigate the course of inflammatory arthritis.
EVALuna2:13286